Contralateral C7 Nerve Root Transfer for Function Recovery in Adults： A Meta-analysis - Li, Wen-Jun; He, Li-Yue; Chen, Shan-Lin; Lyu, Yan-Wei; Wang, Shu-Feng; Yong, Yang; Tian, Wen; Tian, Guang-Lei; Gu, Yu-Dong (Chinese medical journal, 2017)
Background：Root avulsion to all 5 roots of the brachial plexus is a common presentation and keeps a major reconstructive challenge.The contralateral C7 （CC7） nerve transfer has been used in treating brachial plexus avulsion injury （BPAI） since 1986.However,the effectiveness of the procedure remains a subject of controversy.The aim of this meta-analysis was to study surgical outcomes regarding motor and sensory recovery after CC7 nerve transfer.Methods：Chinese or English （i.e.,＂contralateral c-7＂,＂contralateral c7＂,＂c7 nerve root＂,and ＂seventh cervical nerve root＂） keywords were used for a literature search for articles related to CC7 nerve transfer in several databases （i.e.,PubMed,Cochrane,Embase,CNKI,CQVIP,and Wanfang Data）.Clinical research articles were screened,and animal studies as well as duplicate publications were excluded.Muscle strength and sensory recovery were considered to be effective only when the scores on the United Kingdom Medical Research Council scale were equal to or higher than M3 and S3,respectively.Results：The overall ipsilateral recipient nerve recovery rates were as follows：the efficiency rate for muscle strength recovery after CC7 nerve transfer was 0.57 （95% confidence interval [CI]：0.48-0.66） and for sensory recovery was 0.52 （95% CI：0.46-0.58）.When the recipient nerve was the median nerve,the efficiency rate for muscle strength recovery was 0.50 （95% CI：0.39-0.61） and for sensory was 0.56 （95% CI：0.50-0.63）.When the recipient nerve was the musculocutaneous nerve and the radial nerve,the efficiency rate for muscle strength recovery was 0.74 （95% CI：0.65-0.82） and 0.50 （95% CI：0.31-0.70）,respectively.Conclusions：Transfer of CC7 nerves to musculocutaneous nerves leads to the best results.CC7 is a reliable donor nerve,which can be safely used for upper limb function reconstruction,especially for entirely BPAI.When modifying procedures,musculocutaneous nerves and median nerve can be combined as recipient nerves.